The first ethnic Asian case report of Paget’s disease with concomitant primary and secondary hyperparathyroidism - Nantaporn Siwasaranond (2019)
© 2018, Medical Association of Thailand. All rights reserved. The authors report a case of Paget’s disease [PD] with concomitant primary hyperparathyroidism [PHPT] in a 63-year-old Thai female who presented with elevation of alkaline phosphatase [ALP] from the routine annual check-up. The plain film and bone scintigraphy revealed a solitary Paget’s lesion, characterized by osteolytic area, thicken cortex and prominent trabeculations in the right proximal femur. Further investigations revealed low level of 25-hydroxyvitamin D [25-(OH)D], elevation of calcium and parathyroid hormone [PTH] levels. A nodule in the right parathyroid gland was found. The serum calcium and PTH turned to normal after removal of the nodule, which was histologically diagnosed as parathyroid adenoma. Bisphosphonate was then given for treatment of Paget’s disease to prevent fracture. The case of Paget’s disease with concomitant parathyroid adenoma has not been previously reported in ethnic Asian groups. It is important to address that this concomitance is possible even in the countries where Paget’s disease is rare, so that appropriate management is not overlooked.